Implicações da programação pré-natal sobre o desempenho subsequente, características de carcaça e qualidade de carne em suínos - Ana Luisa Neves Alvarenga (2011)
The objective of the present study was to investigate the influence of pre-natal programming on postnatal development, carcass traits and meat quality in pigs. Two hundred and eighty new-born male piglets (DanBred x PIC terminal line), born to 4th- 6th parity sows and in litters of 10 to 15 pigs, were identified as falling into two birth weight groups: high (HW: range 1800 to 2200 g) and low (LW: range 800 to 1200 g). One sub-set of 20 animals from each group was necropsied at birth and the heart, pancreas, liver, spleen, small intestine, large intestine, kidneys, testes, semitendinosus muscle and brain were weighed. Evidence of intra-uterine growth retardation (IUGR) was analyzed by comparing brain:organ weight ratios. The second sub-set of HW (n=120) and LW (n=120) piglets was reared until the finisher period (~150 days of age) and data on growth performance, carcass traits and meat quality were collected. Samples of the semitendinosus muscle and the duodenum from new-born and 150 d animals were collected for histomorphometrical analysis. All organs of HW pigs were heavier than in LW counterparts (P<0.01). Overall, birth weight was more strongly correlated to liver weight (r = 0.91; P<0.01) than to brain weight (r = 0.40; P<0.01) and all brain:organ weight ratios were negatively impacted in LW vs. HW offspring, providing strong evidence of IUGR and prenatal programming in the LW piglets. Moreover, HW pigs had higher body weights and average daily gains (ADG) in all phases (P<0.05), but in the finisher phase, where ADG was similar between both experimental groups. The histomorphometrical analysis showed a lower muscle fiber number per mm2 in the semitendinosus muscle and a lower height of the duodenum mucosa (P<0.05) in new-born and 150d LW pigs. In relation to carcass traits, HW pigs had higher hot carcass weight, meat content in the carcass and yield of ham, shoulder and belly (P<0.01). Despite some differences in carcass traits, birth weight had minor impacts on meat quality, which were limited to a higher shear force in the LW group (P<0.01). In conclusion, the results of this study show that lighter birth weight piglets may suffer from pre-natal programming and IUGR, which have long lasting effects over their productive life. These effects impair their post-natal growth performance and carcass traits, however have limited impacts on meat quality. Hence, the cost/benefit value of rearing low birth weight piglets to market weight must be taken into account when keeping them in the herd.